2013
DOI: 10.1038/icb.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

The developing schistosome worms elicit distinct immune responses in different tissue regions

Abstract: Schistosome parasites follow a complex migration path through various tissues, changing their antigenic profile as they develop. A thorough understanding of the antibody response in each tissue region could help unravel the complex immunology of these developing parasites and aid vaccine design. Here we used a novel strategy for analysing the local antibody responses induced by Schistosoma japonicum infection at each site of infection. Cells from rat lymph nodes draining the sites of larval migration (the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 48 publications
(75 reference statements)
0
43
0
Order By: Relevance
“…Axillary and inguinal lymph nodes (LN) (skin LN) and mediastinal LN (lung LN) were isolated from an uninfected control group and from two groups of rats at 5 and 9 days after secondary infection, respectively. The timing of the isolation of LN corresponded to the expected peak in antibody production in the skin (5 days postinfection) and lung (9 days postinfection) LN (10). The LN were dissected, and cell suspensions were made and cultured at 37°C and 5% CO 2 for 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Axillary and inguinal lymph nodes (LN) (skin LN) and mediastinal LN (lung LN) were isolated from an uninfected control group and from two groups of rats at 5 and 9 days after secondary infection, respectively. The timing of the isolation of LN corresponded to the expected peak in antibody production in the skin (5 days postinfection) and lung (9 days postinfection) LN (10). The LN were dissected, and cell suspensions were made and cultured at 37°C and 5% CO 2 for 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…ASC probes were produced as described previously (10). In short, a Chinese strain of Oncomelania hupensis snails (Anhui Province, People's Republic of China) was used to obtain S. japonicum cercariae, which were subsequently used for the infection of female Wistar rats.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that a major part of the host immune response to infection is directed against carbohydrate (glycan) antigens in glycoproteins and glycolipids (10)(11)(12)(13)(14)(15)(16)(17). A wide variety of unusual antigenic determinants include glycans containing the LDN, fucosylated LDN sequences (LDNF, LDN-dF, FLDN, and FLDNF), Lewis X (Le x ), poly-Le x , core ␣3 fucose, and core ␤2 xylose structures ( Fig.…”
mentioning
confidence: 99%